The Impact of Reward, Punishment, and Motivation on Teacher Performance in Vocational Schools - Noormalita Primandaru; Theo Hangga Agusta (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine how much influence reward, punishment, and motivation have on teacher performance at SMK Negeri Yogyakarta. The data source used in this study is primary data. The sample in this study were teachers at Yogyakarta State Vocational Schools who already had at least one year's work experience. The number of samples obtained was 100 respondents with a purposive sampling technique because the sample selection was based on certain criteria. The data collection technique was carried out by distributing questionnaires online and offline. The analytical method used multiple linear regression with the results of data processing using SPSS 15. The results showed that the reward, punishment, and motivation variables partially had a positive and significant effect on teacher performance at Yogyakarta State Vocational School.